The Use of High-Speed Imaging Systems for Applications in Precision Agriculture - Hijazi, Bilal; Decourselle, Thomas; Minov, Sofija Vulgarakis; Nuyttens, David; Cointault, Frederic; Pieters, Jan; Vangeyte, Jürgen (IntechOpen, 2012)
None